Where the Indus is Young : A Winter in Baltistan - Murphy, Dervla (London John Murray, 1977)
Kashmir - description and travel.
Include Illustrations, Glossary, Bibliography and Index.
Keywords: Travel -- Pakistan--Baltistan -- Murphy, Dervla -- India--Jammu and Kashmir